De la haine au crime - Charles de Lespinay; Frank Alvarez Pereyre (Droit et Cultures)
How does one turn a criminal on the basis of hatred? How such an offense is to be dealt with, beyond punishment? With a genuine consideration for a restorative approach, how should we consider prejudices and hatred in the framework of the formal performance of law? And to what extent any offense of that kind can be atoned? Offenses based upon hatred might refer to criminal actions performed by an individual against another person that is felt to be different, and also to mass actions for which such terms as “genocide”, “crimes against humanity”, and “war crimes” have been coined. Actually one has to clarify both hatred as a behavior - its roots and justifications -, and the very notions of offense and crime. As a legal concept Lex talionis does not call for revenge. By the moment the very notion of difference gives ground to criminal acts, one has to better understand what is actually called stereotypes and prejudices, and how law should find its way when facing such developments. Restorative justice and distributive justice confront the victims - these persons belonging to a group which does exist as such or that is only said to exist -, the “perpetrators” and the ways law and society do handle these protagonists. All these issues are of a great concern for the anthropologists and for those dealing with law, as well. Such issues call for a genuine consideration for the notion of “difference”, for the complex question of the Other and for the one pertaining to Humanity. As for the jurist, he is often facing quite unusual situations where ideology and ethnography have their say. He is then bound to an unending movement, through which he is led to inquire again and again about the notions of crime and hatred. So as to garantee and preserve the central place which is deemed to the Human value of Mankind, whenever a person is attacked and turns to be a victim.